The Impact of Covid-19 Pandemic Towards Stock Return in Indonesia : (Empirical Study On Companies Listed In IDX During Period Of 2019–2020) - Jaunanda, Meiliana; Gabrielle Angelica Beatrice Inzen (Universitas Pelita Harapan, 2024)
This research was conducted to analyze the impact of Return on Asset (ROA), Market Capitalization, COVID-19 Pandemic, and Stock Sector towards Stock Return in Indonesia. The independent variables used in this study are Return on Asset (ROA), Market Capitalization, Daily Increase of COVID-19 Total Confirmed Cases, and Stock Sector as a dummy variable. The control variables used in this study are Debt-to-Equity Ratio (DER) and Company Size. The dependent variable used in this study is Stock Return. The population of this study is the companies that are listed in Indonesia Stock Exchange (IDX) during 2019 and 2020. A total of 776 samples are collected based on the purposive sampling method used in this study. The results showed that: (1) Return on Asset (ROA) has a significant positive impact towards stock return; (2) Market Capitalization has a significant positive impact towards stock return; (3) Daily Increase of COVID-19 Total Confirmed Cases has a significant negative impact towards stock return; and (4) Stock Sector has an insignificant negative impact towards stock return.